Community and student collaboration to help stunted children in Bojong village Cianjur district - Ibrahim, Fahmi; Salsabila, Hasna Raina (Universitas Pendidikan Indonesia, 2024)
The pervasive issue of stunting poses a significant threat to the holistic development of children, affecting both their physical and cognitive well-being and, consequently, their prospects. To combat this challenge, a community service group from UPI initiated the Sipenting program (Students Concerned about Stunting). This program, executed in RW 14 of Bojong Village, Cianjur District, adopted diverse strategies, such as home visits and distributing essential groceries to families with stunted children. The primary goal was to enhance awareness regarding stunting and contribute to its reduction in the Cianjur region. The community's active engagement and remarkable enthusiasm were distinctive features of this initiative's impact. Beyond instilling a sense of responsibility, the program fostered collaborative endeavors within the community to tackle the persistent stunting issue, showcasing a positive influence on the collective commitment to addressing this concern. Through these concerted efforts, the initiative has demonstrated tangible progress in raising awareness and mobilizing community resources to combat stunting effectively.